How well does foreign direct investment measure real investment by foreign-owned companies? Firm-level analysis - Topias Leino; Jyrki Ali-Yrkkö (Bank of Finland, 2014)
We study Foreign Direct Investment (FDI) as a measure of real investment (gross fixed capital formation) in foreign-owned companies. Our data include firm-level information on FDI in-flows and real investment of foreign-owned companies located in Finland. Our results suggest that the recorded annual inflows of FDI do not constitute an accurate measure of annual real investments in foreign-owned companies. Since the beginning of the global recession in 2008, FDI inflows have significantly underestimated real investments in foreign companies in Finland. We seek to explain these findings by describing Finnish FDI target enterprises and subgroups and the nature of their FDI flows from several perspectives. We show how FDI target enterprises use other sources of funding, in addition to FDI, and how a few large transactions, often related to cross-border mergers and acquisitions, can explain a great deal of the recorded annual FDI flows. We also describe how Finland's FDI stock and flow data increasingly consist of funds that merely pass through the FDI enterprises and subgroups, arguably with little or no real economic linkage to the Finnish economy, and we present a method for estimating such pass-through funding.
URN:NBN:fi:bof-20140807356
Keywords: F21; F23; E22; 330; Foreign Direct Investment; Gross Fixed Capital Formation; Investment; Measurement; Pass-through Investments